Diversity and dominance of flora around wetlands in Lakkavalli Range of Bhadra Wildlife Sanctuary, Karnataka - and Pramod, A.F., Vijaya Kumara*, Raghavendra Gowda, H.T., (International Multidisciplinary Research Journal, 2011)
The present communication is based upon a research work and the building a database for plants in the wetlands of Lakkavalli range of Bhadra Wildlife sanctuary. From these wetlands, about 133 species of plants have been identified of which herbs (27), shrubs (22) climbers (19) and trees (65).The objective of the work was to help wetland managers and ecologists by providing an account of the floral characteristics around wetland community.